A Study of Student’s Perceptions towards Online Distance Learning during Lockdown Period of COVID-19 Pandemic - Nurul - Aryanti; Welly Ardiansyah (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2020)
Ensuring the quality of online distance learning in institutions of higher education has been a growing concern during the Covid-19 pandemic. This research was conducted on students’ perceptions toward the quality of online distance learning and utilized qualitative and quantitative methods to investigate the perceptions of students. To collect the data, the researchers used a modified questionnaire. Survey analysis was carried out. A total of 570 students from two study programs, Public Sector Accounting and Business Administration at State Polytechnic of Sriwijaya, were asked to answer a questionnaire. The findings of this research revealed that majority of students considered the use of online distance learning in English teaching and learning is effective and efficient in terms of time. The online distance learning is the best choice to keep students away from the COVID-19 pandemic spread. The findings can be used by any lecturers to understand students’ perceptions regarding online distance learning, and ultimately improve their online distance learning instructional practices.